Emergency medicine on CD-ROM (Philadelphia : Lippincott- Raven, 1997)
Featuring contents of: Clinical Practice of Emergency Medicine, 2nd ed. (Harwood-Nuss); Manual of Skin Diseases, 7th ed. (Sauer, Hall); Wills Eye manual, 2nd ed.; Lippincott's Nursing Drug Guide 1997 (Karch); Medline Subset and Video (Chapman, Levitan).
CD is available at Koleksi Media Perpustakaan HUKM
Provides an access acurate on emergency medicine information
System requirements: Windows:MS-DOS 5.0 and Windows 3.1 or higher (Windows 95 compatible); 80406 33MHz with 8MB RAM; 2MB free hard disk space; double speed CD-ROM drive; 256 color graphics card and monitor.
System requirements: Macintosh: System 6.8 or higher; 68040 machine with 8MB RAM; 5MB free hard disk space; double speed CD-ROM drive; 256 color graphics display.
Keywords: Emergency Medicine -- CD-ROM